LINEAGE SWITCH LEUKEMIA LIMFOBLASTIK AKUT MENJADI LEUKEMIA MIELOMONOSITIK AKUT PADA PEREMPUAN USIA 26 TAHUN (Lineage Switch From Acute Lymphoblastic Leukemia To Acute Myelomonocytic Leukemia at A 26 Years Old Woman) - Burhanuddin Said; Maimun ZA; Budiman Budiman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
A lineage switch from Acute Lymphoblastic Leukemia (ALL) to Acute Myeloid Leukemia (AML) is very rare. It was estimated between6− 9% of cases that occurred, especially lineage switch from ALL to Acute Myelomonoblastic Leukemia (AMMOL). The reviewers reporta case of a 26 years old women with the first clinical presentation were fever and double visions and diagnosed as B-Acute lymphoblasticleukemia ALL with CD13 and CD33 expression aberrations, based on Bone Marrow Aspiration (BMA) and immunoprephenotyping inHongkong Hospital. After induction therapy, in the second month, BMA was done and found 10% blast, so it couldn’t be assessed ascomplete remission. After two (2) months, she comes back to Indonesia to follow continuing the treatment. She was suffered from severeheadache and blurred vision. The blast cell morphology of BMA showed myeloblast 25% and monoblast 60%, consistent with the diagnosisof AMMOL. Moreover, both findings were quite specific for each common cell ALL and acute myelomonocytic leukemia. These findingssupport that this case is completely different leukemic clones occurred at each leukemic expression. Exogenic factor such as chemotherapyand endogenic factor due to chromosomal abnormalities is supposed to be the cause of this lineage switch during the treatment.